Feasibility assessment of the implementation of solar and wind energy technologies in the current context of Iran-case study: Kerman - Parapari, Danial Monsefi (Penerbit UTM Press, 2015)
One of the most important issues in various energy issues is to decrease fossil fuel energy usage and promote renewable energies in developing countries. Iran as a developing country began exploiting renewable resources from the early 1990s. This paper investigates the financial viability of renewable energy technologies in Kerman, which is located in the hot and dry parts of Iran and has a high potential of solar and wind energy. First the potential for solar and wind energy sources are studied and afterwards through two quantitative methods, the cost of this implementation is compared to the benefits gained. The results prove that without a massive financial support by the government, renewable energies would not be economically feasible to be implemented into private households